Microstructure and Dielectric Properties of Nickel‐Doped Ba0.7Sr0.3TiO3 Ceramics Fabricated by Solgel Method. Issue 1 (4th June 2015) - Kakumani, Asa Deepthi; Ruthramurthy, Balachandran; Wong, Hin Yong; Ong, Boon Hoong; Tan, Kar‐Ban; Yow, Ho Kwang
Abstract : A study of phase transition, microstructure, and dielectric properties of Ba0.7 Sr0.3 Ti1– x Ni x O3 (BSTN) ceramics prepared by slow‐injection solgel technique with x ranging from 0 to 1 mol% is reported in this article. The as‐prepared BSTN material was calcined at 800 and 1000°C and subsequently sintered at 1100 and 1200°C, respectively. The optimized condition was found to be Ba0.7 Sr0.3 TiO3 doped with 1 mol% nickel calcined at 1000°C and sintered at 1200°C having the lowest dielectric loss of 0.02 with a dielectric constant of 1603 which was measured at a frequency of 1 kHz at room temperature.